2020
DOI: 10.7717/peerj.9032
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of gut microbiota in Tibetan wild asses (Equus kiang) and domestic donkeys (Equus asinus) on the Qinghai-Tibet plateau

Abstract: Tibetan wild asses (Equus Kiang) are the only wild species of perissodactyls on the Qinghai-Tibet Plateau and appears on the International Union for Conversation of Nature (IUCN) 2012 Red List of threatened species. Therefore, understanding the gut microbiota composition and function of wild asses can provide a theoretical for the situ conservation of wild animals in the future.In this study, we measured the dry matter digestion by the 4 molar hydrochloric acid (4N HCL) acid-insoluble ash method and analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 52 publications
10
27
0
Order By: Relevance
“…However, due to the robustness and resilience of the gut microbial community, wild sables can still survive under such conditions. Similar conclusions were reached by previous studies on gut microbiota of black-necked cranes ( Grus nigricollis ) [ 64 ] and Tibet wild asses ( Equus kiang ) [ 70 ] on the Qinghai-Tibet plateau. Taken together, this study shows that wild sables are adaptable to changing conditions and resistant to harsh environments, and that this adaptability is mediated by gut bacterial composition adjustment and metabolic functions enhancement.…”
Section: Discussionsupporting
confidence: 90%
“…However, due to the robustness and resilience of the gut microbial community, wild sables can still survive under such conditions. Similar conclusions were reached by previous studies on gut microbiota of black-necked cranes ( Grus nigricollis ) [ 64 ] and Tibet wild asses ( Equus kiang ) [ 70 ] on the Qinghai-Tibet plateau. Taken together, this study shows that wild sables are adaptable to changing conditions and resistant to harsh environments, and that this adaptability is mediated by gut bacterial composition adjustment and metabolic functions enhancement.…”
Section: Discussionsupporting
confidence: 90%
“…The furcosa_group that is member of the phylum Firmicutes , was the inferred keystone genus in the stomach and the large intestine. The furcosa_group did not predominate in the GIT, a result that is consistent with previous studies [ 70 ] that showed that the keystone genus was not always the predominant genus. Rikenellaceae_RC9_gut_group was the inferred keystone genus in the small intestine and the Rikenellaceae_RC9_gut_group was the main member of the phylum Bacteroidetes .…”
Section: Discussionsupporting
confidence: 92%
“…However, limited information is currently available regarding donkey intestinal microbial composition and its potential metabolic impact. A few studies have focused on the fecal microbial composition of donkeys (Liu et al, 2014(Liu et al, , 2020, and a recent study has investigated the microbial composition and functions of digestive tract digesta in the Dezhou donkey (Liu et al, 2019). To our knowledge, no work has reported on the differences of digesta-and mucosa-associated microbiota in the different intestinal locations in the donkeys.…”
Section: Introductionmentioning
confidence: 99%